Perlindungan Hak Atas Kebebasan Berkeyakinan dan Beragama bagi Kelompok Minoritas Agama dan Aliran Kepercayaan di Provinsi Sulawesi Utara - Oksimana Darmawan (Jurnal HAM, 2012)
Problems of this study, are 1) how the regulations on the protection of minority rights for religious groups and cult in the local regulations at the provincial level; 2) whether the existing regulations in line with the instruments on Human Rights; and 3) how the reality community life in the context of inter-religious harmony.The purpose of this study, are 1) to find out about the regulations on freedom of belief for religious minorities and the flow of trust in local regulations that exist; 2) to determine whether there is regulation in areas that are contrary to human rights instruments in terms of freedom for minorities religion and cult; and 3) to know the reality of community life in the context of inter-religious harmony.  The method is descriptive qualitative research, ie research that produces descriptive data in the form of words written or spoken of the people and behaviors that can be observed. Conclusion this study is, 1) regulatory policies that govern the freedom of religious communities in North Sulawesi (North Sulawesi consists of six religions, namely: Islam, Catholicism, Protestantism, Buddhism, Hinduism, and Confucianism), as long as there has been no reports of practice discrimination among religions; 2) human rights instruments in the context of religious harmony have been accommodated in one of the principles of human rights, namely participatory manner interfaith cooperation through the forum Interfaith Cooperation Agency and the Forum for Religious Harmony; and 3) the reality community life in the context of inter-religious harmony bound by kinship who get along.